Chalcogen‐Containing Diols: A Novel Chiral Derivatizing Agent for 77Se and 125Te NMR Chiral Recognition of Primary Amines. Issue 16 (26th April 2019) - Lima, Yanka Rocha; Peglow, Thiago Jacobsen; Nobre, Patrick Carvalho; Campos, Patrick Teixeira; Perin, Gelson; Lenardão, Eder J.; Silva, Márcio S.
Abstract: In this work, a novel chiral diol containing a chalcogen was developed for the 77 Se and 125 Te NMR chiral recognition of racemic primary amines. The enantiopure chiral derivatizing agents were synthesized from a readily available and versatile ( S )‐solketal reagent. The synthesis was performed in three steps with satisfactory yields. The chiral derivatizing agents containing selenium or tellurium nuclides were evaluated for effective NMR chiral discrimination of racemic primary amines by a simple three component chiral derivatization protocol through the modified James‐Bull method. The split 77 Se and 125 Te NMR signals are well‐distinguishable and greater than 1 H NMR signals. The Nuclear Overhauser Spectroscopy (NOESY) NMR 2D analysis and semi‐empirical method suggest a conformational preference of diastereoisomers, that provide information of the absolute configuration using selenium and tellurium chiral derivatizing agents. Abstract : In this contribution, a novel chiral diol containing chalcogen atom was developed for 77 Se and 125 Te NMR chiral recognition of racemic primary amines. The CDAs were synthesized from a readily available and versatile ( S )‐solketal starting material.